ENTERPRISE RESOURCE PLANNING SYSTEM, UNRAVELING THE EVOLUTION AND TRANSFORMATIVE IMPACT ON PT. XYZ - Fajar Kholillulloh; Hilma Tsani Amanati; Nandya Octanti Pusparini; Bella Ananda Chairunnisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In an era of rapid technological growth, data and information have become vital for businesses. To effectively manage large volumes of data and integrate information across various departments, an Enterprise Resource Planning (ERP) system is essential. However, the implementation of ERP poses challenges as it requires careful consideration of economic, technical, and technological factors. This research seeks to analyze the effects of ERP implementation on the financial performance of companies, specifically focusing on PT. XYZ, a medical equipment distributor in Indonesia. A qualitative descriptive methodology is utilized to explore how ERP supports data management and handles increases in transaction volume. Implementations of ERP systems, such as Odoo, offer significant advantages, including the capability to generate real-time financial reports and track cash flow in line with the company's logistics activities. Nevertheless, the ERP implementation process demands considerable time and effort from management to ensure accurate and consistent data entry.